Effect of Different Diets on the Biology of Fig Moth Ephestia cautella (Walk.) (Lepidoptera : Pyralidae) - Aziz, F.M.; Hameed, S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Results indicated that different diets significantly affected the development and survival of fig moth Ephestia cautella (Walk.) in laboratory . Egg incubation was ranged between 3.9 and 4 days , while egg production means were (130.5 , 126, 118.9 , 68 , 60.8 and 58) eggs frwed . Hatching percentages were (79.87% , 80.2% , 75.7% , 75.1% , 74.9% and 75%) on diets containing dates , ground wheat fig. raisin , currant and dryapriocot , respectively . Results of this study showed that the shortest generation period was obtained when insects were reared on diet containing ground wheat , while the longest generation period was record for insects reareded on dates.